Análises populacionais em Trypanosoma cruzi baseadas em microssatélites polimórficos de DNA - Helder Magno Silva Valadares (2007)
Chagas disease caused by the protozoan Trypanosoma cruzi exhibits distinct clinical manifestations resulting from complex interactions among environmental and genetic factors from both host and parasite. Concerning the parasite genetic factors, a broad range of biological and molecular studies has revealed substantial genetic variability among T. cruzi strains. Microsatellite profiles analysis is a powerful technique to access genetic variability in eukaryotes, and can be used to distinguish individuals or populations of different species. Previous studies usingeight dinucleotide microsatellite loci have provided valuable information about the structure of T. cruzi populations. However, because of the methodology used to isolate these loci, the sequences flanking of the repeats are very short, which makes the design of adequate primers to achieve good amplifications by PCR a difficult task. In addition, dinucleotide loci are especially susceptible to DNA polymerase slippages, which complicate the amplicon analyses. In the present work, we describe new microsatellite loci suitable to T. cruzi characterizationdirectly in biological samples that usually present very little parasite DNA. For that, and taking advantages from the T. cruzi genome sequencing project, we evaluate the abundance, composition and distribution of perfect microsatellites constituted of di, tri and tetranucleotide motifs in the T. cruzi genome. In general, the microsatellite loci were 12 times less frequently in coding regions compared to noncoding regions of the T. cruzi genome, where the dinucleotide repeats were the most abundant (47,6%). However, the trinucleotide repeats were the most common microsatellite within the coding regions. Using the software TandemRepeats Finder it was possible to identify and characterize seven new microsatellite loci six composed by trinucleotide (TcTAC15, TcTAT20, TcAAT8, TcATT14, TcGAG10 and TcCAA10) and one composed by tetranucleotide motifs (TcAAAT6). All, except the TcCAA10 locus, were physically mapped on distinct intergenic regions of the chromosome III of the CL Brener. Contrasting, the TcCAA10 locus was localized within a hypothetical protein gene in T. cruzi genome. All microsatellites were polymorphic and useful for T. cruzi genetic variability studies. Remarkable results were obtained by analyzing the allele sizes of the amplicons for the TcTAC15 locus. By using this locus it was possible to separate the strains belonging to T. cruzi I lineage from those belonging to T. cruzi II, T. cruzi III and hybrid group. To establish a more sensitive PCR assay, we designed extra pairs of primers for each microsatellite locus and used them in Full Nested PCR protocols. By using this strategy we could detect and differentiate T. cruzi strains directly in human and animal infected tissues. Besides, it was also possible to amplify the parasite DNA directly in single cells separated by FACS Cell Sorter. To achieve that, the current procedure for single cells separation by FACS Cell Sorter was optimizedand a multiplex PCR assay was described. Up to now two artificially (JG+Col1.7G2 and SilvioX10 cl1+Esmeraldo cl3) and two naturally (Berenice-78 25B and A316A R7) mixed populations were analyzed after single cell sorting. In all cases we could separate and identify the subpopulations present in the polyclonal populations. The Be-78 25B isolate was composed by at least two clones: one similar to the Berenice-62 strain and belonging to T. cruzi II major lineage (DTU IIb) and another belonging to the hybrid group (DTU IId). The isolate A316A R7 was also constituted by two clones: one belonging to T. cruzi I (DTU I) and another belonging to T. cruzi II lineage (DTU IIb). Finally, in the present work, we analyzed cases of congenital Chagas disease from three distinct endemic regions (Minas Gerais and Rio Grande do Sul, Brazil, and Buenos Aires, Argentine). The microsatellite profiles showed a perfect genotypic identity between the mothers-offspring pairs analyzed, in agreement with the diagnose of congenital infection for these cases. The microsatellite analyses associated to other markers evolutionarily more conserved in T. cruzi (rDNA 24S, COII and mini-exon) showed that in the Minas Gerais state the isolated parasites of all congenital cases belong to T. cruzi II lineage (DTU IIb), whereas the isolated parasites from congenital cases from the Rio Grande do Sul state and Argentine belong to hybrid strains group (DTU IId). It is interesting that the prevalence of congenital cases of Chagas disease in south part of Brazil and Argentine seems to be much higher than in Minas Gerais. Thus, we hypothezed thatthe high frequency of congenital cases of Chagas disease in an endemic area is associated with the higher predominance of T. cruzi hybrid populations (especially from the DTU IId) circulating in this region.